Educating for change - enabling local implementation of the United Nations' sustainable development goals in Cameroon - Ian Brooks; Mario Kossmann; Virginie Kossmann (Project Management Research and Practice, 2018)
The United Nations' Sustainable Development Goals (SDGs) framework was adopted by every member state of the United Nations in 2015, and, albeit not legally binding, it is arguably one of the most significant steps of humanity to address the identified problems of our time. It addresses a wide range of topics such as environmental protection, equal opportunities, education, eradication of diseases, famine, poverty, slavery and child labour. Both concerning its comprehensive scope and its worldwide support, this framework arguably represents one of the most significant international frameworks in human history. Using education-related examples from a charity project related to a local health care system in the African rain forest in Cameroon, this paper illustrates how projects can and should implement critical aspects of the SDGs framework pre-emptively within their scope. This could be at the local level, before and in support of the full, legally binding implementation of the framework at the national level. This not only helps to make our world a better place but also very concretely to reduce project risks, create funding opportunities and make the project's deliverables more sustainable. The 'Mahola Project' ('Mahola' means 'Aid' in the local Bassa language) was founded in 2013 - following an exploration trip to Cameroon in order to assess the real needs of the population in the deprived area around the village Siliyegue - as a response to meet these needs. The main objective of the project is the development and deployment of a sustainable, integrated, local health care system that is fully aligned with the SDGs and brings about dramatic improvements for the quality of life of the people living there; far beyond 'just' providing health care and work opportunities. Education is at the core of the necessary efforts to successfully deliver this system, changing minds and hearts.